The Palestinian-Israeli conflict: a comparative analysis on the language of occupation - Abdul Latiff@Bapoo, Lili Suriani; Majelan, Syareen Izzaty (International Digital Organization for Scientific Information (IDOSI), 2014)
The Palestinian-Israeli conflict and the issue of Israeli occupation of Palestinian territories have not been resolved since the 1940s. Despite efforts for reconciliation, the Israelis and Palestinians are yet to reach a final peace agreement. A wide variety of views and opinions have been expressed on the issue but it remains a question of how both Palestinian and Israeli societies have communicated on it. This paper analyzed the language discourse of 10 texts-2 speeches by the countries’ political leaders, 4 online newspaper articles and 4 online articles written by Palestinian and Israeli writers. A comparison was then made on the discourses used by both parties. The study found that similar forms of racial discourse to justify their feelings of prejudice of each other were used in political speeches and online texts. While the discourse of power was obvious in the political speeches, the discourse of prejudice was amplified in the online newspapers and articles.